2002
DOI: 10.1097/00001665-200207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Endo-Orbital Osteoma: Two Case Reports

Abstract: Osteoma is a benign, slow-growing tumor, which mainly occurs in the bones and cavities of the middle third of the face, representing the most frequent benign tumor of the paranasal sinuses. Osteoma of the paranasal sinuses is generally asymptomatic and it is discovered only as a coincidental radiological finding; when it becomes symptomatic, the most common presenting symptoms are headaches and facial pain. Rarely the sinusal osteoma may entail secondary orbital extension, with ocular signs and symptoms. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Although osteomas can develop at any age, they seem to be more common among young adults [2,3,8,12]. Nevertheless, in other studies, higher frequencies of occurrence between the third and fifth decades were reported [7,11,13]. In agreement with this statement, our patient was in his fifth decade.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although osteomas can develop at any age, they seem to be more common among young adults [2,3,8,12]. Nevertheless, in other studies, higher frequencies of occurrence between the third and fifth decades were reported [7,11,13]. In agreement with this statement, our patient was in his fifth decade.…”
Section: Discussionsupporting
confidence: 88%
“…Radiographic findings usually describe osteomas as radiopaque masses with a density similar to that of bone [7,11]. Some authors [2,17] consider that CT, especially with 3D reconstruction, is the best imaging modality for a diagnosis of peripheral osteoma [7,11,13]. In our case, the osteoma was detected with panoramic and TMJ radiographs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Osteomas are the most frequent benign tumors of the paranasal sinuses, occurring most commonly in the frontal sinus. [10] Peripheral osteomas of the jaws are uncommon [9] and more often found in the mandible than in the maxilla [5]. Lingual aspect of the mandibular body and the inferior border of the angle are the most common sites affected in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Остеома нередко является случайной находкой: в 1% случаев при рентгенографии и в 3% -при ком-пьютерной томографии (КТ) околоносовых пазух [5] у пациентов в возрасте от 10 до 50 лет. Крайне редко остеомы выявляют у детей [6].…”
unclassified